SINGLE-CRYSTAL ELASTICITY OF ZOISITE CA2AL3 SI3O12(OH) BY BRILLOUIN SCATTERING - Mao Z.; Jiang F.; Duffy T.S. (My University, 2007)
The single-crystal elastic constants of zoisite Ca2Al3Si3O12(OH) were determined by Brillouin scattering at ambient conditions. The elastic tensor was obtained by an inversion of acoustic velocity data for three different crystal planes. The aggregate bulk modulus, shear modulus, and Poisson's ratio are KS0 = 125.3(4) GPa, G0 = 72.9(2) GPa, and σ0 = 0.26(1) for the VRH (Voigt-Reuss-Hill) average, respectively. The maximum azimuthal anisotropy of zoisite is 22% for compressional velocity and 33% for shear velocity. The maximum shear splitting is 21% along the [001] direction. Our results resolve the discrepancies in bulk modulus and axial compressibilities reported from static compression studies, and provide the first experimental constraints on the shear modulus. Trends in the elastic moduli of minerals in the CaO-Al2O3- SiO2-H2O (CASH) system are evaluated.
Keywords: BRILLOUIN SCATTERING; ELASTICITY; SINGLE CRYSTAL; ZOISITE